Cinematic Metaphors in Jokowi’s International Political Speeches: A Conceptual Metaphor Theory Analysis - Nana Asrianti; Dyah Sunggingwati; Noor Rachmawaty; Iwan Setiawan; Ventje Jany Kalukar; Istanti Hermagustiana; Sunardi Sunardi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Language plays a central role in political communication, particularly through the use of metaphor, which enables leaders to simplify complex issues and influence public perception. In the digital era, cinematic metaphors drawn from popular films and television series have become increasingly visible in political discourse. This study examines cinematic metaphors in two of President Joko Widodo’s international speeches delivered in 2018. Using a descriptive qualitative design, the analysis applies Conceptual Metaphor Theory and Critical Metaphor Analysis to identify and interpret metaphors derived from Avengers: Infinity War and Game of Thrones. Fourteen cinematic metaphors were identified and categorized into four conceptual mappings: ECONOMIC CONFLICT IS WAR, LEADERS ARE HEROES, ECONOMIC UNCERTAINTY IS NATURAL DISASTER, and INTERNATIONAL RELATIONS ARE A GAME OF POWER. The findings show that these metaphors function not only as linguistic devices but also as rhetorical strategies that construct meaning, highlight global risks, and legitimize Jokowi’s call for cooperation. The study concludes that cinematic metaphors enhance accessibility and emotional resonance in political messaging by connecting global issues with familiar cultural narratives. The originality of this research lies in its focus on cinematic metaphors in Indonesian political speech—an area rarely examined in prior studies—and its integration of cognitive and rhetorical perspectives to explain how popular culture shapes contemporary political discourse.